Analisis Peran Puskesmas Medan Amplas dalam Meningkatkan Kesehatan Masyarakat di Wilayahnya - Yeni Sabariah Nasution; Mami Azzahra Lubis; Vazira Nurul Assyfa; Fika Ayu Cahaya Hsb; Widya Sari; Rani Suraya (Sagita Academia Journal, 2025)
This study aims to analyze the role of Medan Amplas Public Health Center (Puskesmas) in improving community health in its area. The method used is descriptive qualitative through interviews, observations, and document studies. The results show that Medan Amplas Puskesmas performs promotive, preventive, curative, and rehabilitative functions through programs such as immunization, treatment of infectious diseases, and maternal and child health services. Challenges such as limited infrastructure, low public awareness, and a lack of human and financial resources are the main obstacles. The strategies implemented include cross-sector collaboration, community education, and the establishment of health emergency posts in flood-affected areas.